2007
DOI: 10.1144/0016-76492005-190
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous granitic plutons from the northern margin of the North China block: implications for a late Palaeozoic active continental margin

Abstract: We report four late Palaeozoic zircon sensitive high-resolution ion microprobe (SHRIMP) U-Pb ages for granitic plutons from the Inner Mongolia Palaeo-uplift on the northern margin of the North China block. These cast a new light on the poorly understood tectonic history of the northern margin of the North China block and the Central Asian Orogenic Belt during the late Palaeozoic. The plutons have for a long time been considered to belong to the early Precambrian basement of the North China block. Our new SHRIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(197 citation statements)
references
References 39 publications
3
188
0
6
Order By: Relevance
“…The field of the southeastern Central Asian Orogenic Belt (CAOB) is modified after Yang et al (2006). Literature data include the Yinshan-Yanshan Orogenic Belt (YYOB) (Zheng et al, 2004;Tian et al, 2007;Zhang et al, 2007bZhang et al, -d, 2009cMa and Zheng, 2009;Shi et al, 2010), the Ordovician-Silurian granitic plutons of the Northern Qinling Orogen (NQO) (Wang et al, 2009) Fig. 3e and f; 7 grains) is less than that in sample J-7 and N-4 ( Fig.…”
Section: Early Late Triassic Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of the southeastern Central Asian Orogenic Belt (CAOB) is modified after Yang et al (2006). Literature data include the Yinshan-Yanshan Orogenic Belt (YYOB) (Zheng et al, 2004;Tian et al, 2007;Zhang et al, 2007bZhang et al, -d, 2009cMa and Zheng, 2009;Shi et al, 2010), the Ordovician-Silurian granitic plutons of the Northern Qinling Orogen (NQO) (Wang et al, 2009) Fig. 3e and f; 7 grains) is less than that in sample J-7 and N-4 ( Fig.…”
Section: Early Late Triassic Samplesmentioning
confidence: 99%
“…4c; Zheng et al, 2004;Tian et al, 2007;Zhang et al, 2007bZhang et al, , 2007cZhang et al, , 2007dZhang et al, , 2009cZhang et al, , 2009dShi et al, 2010;Yang and Li, 2008;Ma and Zheng, 2009). The NQO is characterized by the Ordovician-Silurian and early Mesozoic magmatic rocks .…”
Section: Potential Source Of the Phanerozoic Zirconsmentioning
confidence: 99%
“…The CAOB is a major Phanerozoic accretionary orogen seated between the European Craton (EC) to the west, the Siberian Craton (SC) to the east, and the NCC to the south (e.g., Windley et al, 2007;Xiao et al, 2009). The accretion process of the CAOB is related to the tectonic evolution of the Paleo-Asian Ocean (e.g., Tang et al, 1990;Han et al, 2011;Xu et al, 2013) and the final closure of the Paleo-Asian Ocean resulted in the amalgamation of the NCC and CAOB during the Late Permian to Triassic (e.g., Xiao et al, 2003, Zhang et al, 2007a, 2009a, 2009bMiao et al, 2008;Jian et al, 2010). In the CABO, the closure of the Mongol-Okhotsk orogen shows a youngering trend from the Permian-Jurassic in the west to Late Jurassic-Early Cretaceous in the east (Zonenshain et al, 1990;Cogné et al, 2005;Tomurtogoo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Paleocurrent analysis revealed that the southern Ordos Basin mainly received easterly and northeasterly derived detritus during the deposition of the lower Yanchang Formation [68], which provides important evidence for the transport of materials from the IMPU to the southern Ordos Basin during the Middle Triassic. Furthermore, the analysis of the sandstones detrital modes indicates the provenance of the lower Yanchang Formation mainly came from the ancient mountains surrounding the basin [52], which is consistent with the tectono-sedimentary setting in the northern margin of NCC where the IMPU had been deeply eroded from the Late Carboniferous to the Early Jurassic [65,66].…”
Section: Discussionmentioning
confidence: 64%